Association between knee alignment, body mass index and physical fitness variables among students: a cross-sectional study Associação entre Alinhamento do Joelho, Índice de Massa Corporal e Variáveis de Aptidão Física em Estudantes. Estudo Transversal - Andréia Araújo Souza; Gerson Luis de Moraes Ferrari; João Pedro da Silva Júnior; Leonardo José da Silva; Luis Carlos de Oliveira; Victor Keihan Rodrigues Matsudo (Revista Brasileira de Ortopedia, 2013)
OBJECTIVE: To assess the association between malalignment of the knees (genu valgum) and variables of physical fitness among schoolchildren. METHODS: We analyzed data collected between the years 2000 to 2009. The sample comprised 1,141 schoolchildren of both sexes aged 06 to 18 years. To participate in the research, the students must meet the following criteria: age between 6 and 18 years and a full assessment of physical fitness, including measurement of genu valgus in at least one of the semester assessments. Postural evaluation (valgus) was determined by the intermalleolar distance, in centimeter. Body Mass Index (BMI) determined through the growth curves of the World Health Organization. Physical fitness variables (strength of upper and lower limbs, agility, speed and flexibility), were taken according to CELAFISCS standardization. RESULTS: Among male students it was found a prevalence of 23.2% obese, 44.4% overweight and 32.4% eutrophic. Among females, the values were: 30.9% obese, overweight 39.5% and 20.6% eutrophic. When analyzing the prevalence of valgus according to the BMI classifications it was, found a significant positive association in both sexes. Association was found between genu valgum and upper limbs strength only in crude analysis. The other variables, agility, speed and flexibility were not associated even when the analysis was adjusted. CONCLUSION: there was a positive association between malalignment of the knees, body mass index and physical fitness among schoolchildren. OBJETIVO: Verificar associação entre o mau alinhamento de joelhos (geno valgo) e variáveis de aptidão física em estudantes. MÉTODOS: Foram analisados dados coletados entre 2000 a 2009. A amostra foi composta por 1.141 estudantes de ambos os sexos, de 6 a 18 anos. Para participar da pesquisa os estudantes deveriam atender os seguintes critérios: ter entre 6 e 18 anos e uma avaliação completa da aptidão física, incluindo a medida de geno valgo. O valgismo foi determinado pela distância intermaleolar, com régua em centímetros. Já para a classificação do Índice de Massa Corporal (IMC) usaram-se as curvas de crescimento da Organização Mundial da Saúde e as variáveis de aptidão física analisadas (força de membros inferiores e superiores, agilidade, velocidade e flexibilidade) seguiram a padronização CELAFISCS. RESULTADOS: No sexo masculino foi encontra uma prevalência de 23,2% de obesos, 44,4% com excesso de peso e 32,4% eutróficos. Entre o sexo feminino, 30,9% eram obesas, 39,5% com excesso de peso 39,5% e 20,6% eutróficas. Quando analisada a prevalência de valgismo de acordo com as classificações do IMC, foi encontrada associação positiva e significativa em ambos os sexos. Foi encontrada associação entre geno valgo à força de membros superiores apenas na análise bruta. As demais variáveis não apresentaram associação. CONCLUSÃO: Houve associação positiva entre mau alinhamento dos joelhos, índice de massa corporal e aptidão física em estudantes.